THE INFLUENCE OF FREE CASH FLOW AND FIRM SIZE ON EARNING MANAGEMENT - Novi Fadhila; Isna Ardila (Proceeding International Seminar of Islamic Studies, 2022)
This research is a causal design research that aims to find out the influence of two or more variables. The variables used are free cash flow and firm size as independent variables and earnings management as the dependent variable on automotive companies listed on the Indonesia Stock Exchange, simultaneously or partially. This research was conducted on 10 automotive companies from 2015 to 2020. The method used in this study is a multiple linear analysis technique. The results of the study show that there is a simultaneous influence between free cash flow and firm size on earning management. The results of the study partially free cash flow affect earnings management, as well as firm sizeKeywords: Free cash flow, Firm Size and Earning Management